Evaluation of Blood Biochemistry and Level Function of Friesian Holstein Dairy Cows Fed UMMB Based on Cocoa Pulp as a Molasses Substitute - Rahman, Andi Arif; Utamy, Renny Fatmyah; Ako, Ambo; Sukri, Siti Annisa; Nurfaisal, Nurfaisal; Hanif, Hanif (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Cocoa pulp is a mucous membrane tissue that wraps cocoa beans and high in carbohydrates that have the potential to substitute the use of molasses in the production of UMMB for FH dairy cows. This study aims to evaluate the effect of molasses substitution with cocoa pulp to produce UMMB on blood biochemistry and liver function of FH dairy cows. This study used a completely randomised design (CRD) with three treatments and five replications. 15 Lactating dairy cows were divided by treatment: no UMMB supplementation (P0); supplementation of 500 g UMMB without molasses filler substitution (P1); and supplementation of 500 g UMMB with 50% molasses filler substitution with 50% cocoa pulp (P2). The treatments had no significant effect (P>0.05) on blood glucose and blood urea levels. The highest blood glucose and urea levels were sequentially obtained in P2, P1 and then the lowest was obtained in P0. The treatment had a significant effect (P<0.05) on SGPT and SGOT levels. The highest SGPT levels were sequentially obtained in P1, P2, and then the lowest were obtained in P0. Then, the highest SGOT levels were sequentially obtained in P0, P2, and the lowest were obtained in P1. The use of 50% cocoa pulp as a substitute for molasses as a filler to produce UMMB does not affect blood biochemical levels and liver function of FH dairy cows.ah FH.